Implementasi Teori Generatif Transformatif Dalam Pembelajaran Bahasa Arab - Abdillah Mahbubi; Nur Aqilah L. R. Opier; Arroyyanah F; M. Yunus Abu Bakar (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
The implementation of transformative generative theory in learning Arabic is an interesting approach in developing Arabic understanding and skills. The transformative generative theory, developed by Noam Chomsky, provides a solid foundation for studying the syntactic structure and transformation of sentences in Arabic. This article reviews the implementation of transformative generative theory in the context of learning Arabic. We explain how this approach can help learners understand the rules of Arabic syntax in a systematic and structured manner. By studying the transformation patterns in Arabic, learners can recognize and apply the correct sentence structure. In addition, the implementation of transformative generative theory in learning Arabic can also help learners expand their vocabulary and improve communication skills. With a deeper understanding of Arabic grammar, learners can construct more complex and accurate sentences. However, it is important to consider individual needs and learning styles in implementing this approach. Every learner has different needs, therefore, teachers and instructors need to provide a learning environment that is supportive and relevant to maximize learner potential